Sistem Pakar Diagnosis Penyakit Karies Gigi pada Anak Usia Dini Menggunakan Metode Forward Chaining - Heni Anggraeni; Ultach Enri; Tesa Nur Padilah (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Dental caries is very common in Indonesian people. 56% of Indonesian people have problems with their teeth, this research started from problems that exist in the Indonesian community so that the idea emerged to create an expert system that can educate the public about dental diseases, especially dental caries. This research was conducted by building an information system regarding dental caries disease information and in it there is an expert system that can be used for consultation. The user system was built using the Forward Chaining method. The Forward Chaining method serves to look for uncertain rules based on the symptoms that arise in people who suffer from dental caries. This the results can be known whether the community suffers from dental caries disease or not. The results of the system testing carried out by the white and black box methods obtained system suitability based on the design requirements through the UML Diagram. Keywords: Forward Chaining, Dental Caries, System Expert